Implementation of Character Education: Perspective of Love for All Hatred For None in Spiritual, Social and Humanitarian Characters Formation in SMU Plus Al-Wahid - Aries Musnandar; Adebayo Rafiu Ibrahim; Abdul Lantong; Sanusi Sanusi; Sutomo Sutomo (Al-Hijr: Journal of Adulearn World, 2022)
This research is motivated by concerns about the high level of violence, hate speech, bullying, and brawls between students in the educational environment, all of which are alarms indicating that Character Education in schools has not been maximized. This type of research is descriptive with an inductive approach to qualitative analysis methods. The data sources in this study are primary data, namely school principals, teachers, students, dormitory builders, and branch administrators of the Wanasigra Ahmadiyya Congregation, while secondary data are lesson plans and various videos on the YouTube channel of SMU Plus Al-Wahid related to the object under study. Data were obtained through observation, interviews, and documentation. The data were then analyzed qualitatively by using triangulation to ensure the validity of the data against the focus understudy. The results of this study were that: (1). Character Education at SMU Plus Al-Wahid was borne from four sources: the Indonesian nation's culture, the Pancasila state basis, Abab 21 demands, and the organizational motto 'Love For All Hatred For None’; (2). Implement Character Education at SMU Plus Al-Wahid through learning, habituation, and example in four activity posts; extracurricular, extracurricular, dorm life, and social activities; (3). A more comprehensive evaluation of character education occurs in schools, dormitories, and community environments; and (4). Implementation of character education from the perspective of the motto 'love for all hatred for none' was developed by the Muslim community of the Indonesian Ahmadiyya congregation to participate in strengthening the character of the nation's children on a communal basis, showing synergy with the community around the school. This study concludes that character education in a community-based school does not have to undermine the cultivation of national character education. Still, it can collaborate with character values ??from organizational wisdom.